Faith and freedom in Galatia and Senegal : the Apostle Paul, colonists and sending gods - Niang, Aliou Cissé. (Biblical Interpretation Series, 2009)
Faith and Freedom in Galatia and Senegal reads Galatians 2:11-15 and 3:26-29 through the lens of the 19th-20th century experiences of French colonialism by the Diola people in Senegal, West Africa, and portrays the Apostle Paul as a \''sociopostcolonial hermeneut who acted on his self-understanding as God's messenger to create, through faith in the cross of Christ, free communities' -- a self-definition that is critical of ancient Graeco-Roman and modern colonial lore that justify colonization as a divine mandate.\' Aliou C. Niang ingeniously compares the colonial objectification of his own people by French colonists to the Graeco-Roman colonial objectifications of the ancient Celts/Gauls/Galatians, and Paul's role in bringing about a different portrayal.